The release of nickel from nickel-titanium (NiTi) is strongly reduced by a sub-micrometer thin layer of calcium phosphate deposited by rf-magnetron sputtering; Journal of Materials Science: Materials in Medicine; Vol. 21, iss. 4 - Surmenev R. A. Roman Anatolievich; Ryabtseva M. A.; Shesterikov E. V. Evgeny Viktorovich; Pichugin V. F. Vladimir Fyodorovich; Peitsch T.; Epple M. (2010, 2010)
Title screen